2007
DOI: 10.1098/rsbl.2006.0593
|View full text |Cite
|
Sign up to set email alerts
|

Nematode parasites reduce carotenoid-based signalling in male red grouse

Abstract: Carotenoids determine the yellow-red colours of many ornaments, which often function as signals of quality. Carotenoid-based signalling may reliably advertise health and should be particularly sensitive to parasite infections. Nematodes are among the commonest parasites of vertebrates, with well-documented negative effects on their hosts. However, to date, little is known about the effects that these parasites may have on carotenoid-based signalling. Tetraonid birds (grouse) exhibit supra-orbital combs, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 19 publications
7
70
1
Order By: Relevance
“…These findings support the idea that sexual displays may signal male infection status as already observed in some biological models (e.g. Hill & Brawner 1998;Brawner et al 2000;Horak et al 2004;Martinez-Padilla et al 2007). Previous studies, including in blackbirds, that used antigenic challenges provided direct support for the idea that immune defences and sexual signals compete for carotenoids (Blount et al 2003;Faivre et al 2003).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings support the idea that sexual displays may signal male infection status as already observed in some biological models (e.g. Hill & Brawner 1998;Brawner et al 2000;Horak et al 2004;Martinez-Padilla et al 2007). Previous studies, including in blackbirds, that used antigenic challenges provided direct support for the idea that immune defences and sexual signals compete for carotenoids (Blount et al 2003;Faivre et al 2003).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, previous experimental studies using parasites have found that (i) controlled infections reduce the expression of carotenoid-based ornamentation (Hill & Brawner 1998;Brawner et al 2000;Horak et al 2004), (ii) parasite eradication positively affects carotenoidbased ornamentation (Martinez-Padilla et al 2007), and (iii) expression level of ornaments may indicate males' ability to clear parasite infection (Lindströ m & Lundström 2000). Furthermore, newly developed methods, which allow measurement of the magnitude of the immune response to various antigens (see Adamo (2004) for a review), made it possible to identify a positive relationship between carotenoid-based coloration and various immune effectors (Blount et al 2003;McGraw & Ardia 2003 and references therein), and have also shown that immune defence and sexual attractiveness are constrained by carotenoid availability (Blount et al 2003;Grether et al 2004;McGraw & Ardia 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The carotenoid-based ornaments of birds are particularly sensitive to parasite infections (Lozano, 1994), as demonstrated with a range of diseases and parasites (e.g. Brawner et al, 2000;Hill et al, 2004;Hõrak et al, 2001;Hõrak et al, 2004;Martinez-Padilla et al, 2007), and should also be sensitive to oxidative stress (Alonso Pike et al, 2007a;von Schantz et al, 1999), itself intimately linked with immune function and disease or parasite resistance (Dowling and Simmons, 2009;Hõrak et al, 2007;Romero et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids might act as significant antioxidants in vivo, thus directly linking ornament pigmentation to resistance to oxidative stress, since more pigmented individuals usually circulate more carotenoids (e.g. Blount et al, 2003;Martínez-Padilla et al, 2007;. Male partridges injected with PHA showed a 13% decrease in circulating carotenoids within 24h .…”
Section: Discussionmentioning
confidence: 99%